Interfacial fracture of the fibre-metal laminates based on fibre reinforced thermoplastics - Abdullah, Mohamed Ruslan (Elsevier, 2015)
As the adhesion quality plays an important role in determining the mechanical performance and environmental stability of most types of fibre-metal laminates (FMLs), investigating the interfacial fracture properties becomes one of the key factors for the improvement. Adhesion of a self-reinforced polypropylene (SRPP) and glass fibre reinforced polypropylene (GFPP) based FML is evaluated experimentally. Single Cantilever Beam (SCB) tests were performed to access interfacial fracture energy (G. c) of the bi-material laminates and their associated interlayer materials. Simulations mimicking the experiments were also performed. The energy needed to fracture was obtained experimentally and also via stress intensity factor from the simulations. The test results show that good adhesion between the aluminium and fibre reinforced thermoplastics can be achieved using a sulphuric acid anodising surface pre-treatment. Further examination has shown that the edges of the test samples highlighted the presence of significant fibre bridging in the SRPP and plastics deformation in the GFPP